Porphyrin-Based Organoplatinum(II) Metallacycles With Enhanced Photooxidization Reactivity - Wu, Lintao; Han, Chun; Wang, Zhijun; Wu, Xi; Su, Feng; Li, Mengyao; Zhang, Qingyang; Jing, Xiaobi (Frontiers in Chemistry, 2020)
In recent years, metal coordination macrocycles have obtained great interests due to they combined the rich host-guest properties of macro-cyclic hosts and the unique optical properties of the organic ligands. In this work, we constructed two porphyrin based organoplatinum(II) metallacycles (MC1 and MC2) through coordination driven assembly. 1H NMR, 31P NMR and HRMS technologies were used to characterize the structures of MC1 and MC2. Interestingly, MC1 and MC2 can be used as catalyst for photooxidization under light irradiation with higher efficiency compared with porphyrin ligand. We hope the coordination driven assembly strategy can provide an efficient method to construct photo-active materials.